Deciphering Resistance Patterns: A Bibliometric Review of Organizational Change in Digital Transformation - Margarita NAZIROVA (Communications of International Proceedings, 2023)
A critically important aspect of modern society is the digitalization of production. However, almost every company in its practice faces resistance to changes among employees during the implementation of digitalization projects. Exponential growth of technological progress forces companies to search for new methods of overcoming constantly emerging barriers in the implementation of digital transformation. In the context of the need for technology development, there is currently an increase in the number of high-tech projects related to the absorption of IT startups. Within the framework of this work an attempt has been made to classify the causes of resistance to digitalization of employees using bibliometric data analysis.
Keywords: resistance to change; bibliometric data analysis; digitalization